A Numerical Study of Bracketing Root-Finding Methods for Nonlinear Equations: Applications to Break-Even Point Determination - Ismuniyarto, Ismuniyarto; Pinheiro, David; Sokhna, El Hadji Lamine (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to compare the results of the Bisection Method, the Regula Falsi Method and the Secant Method in completing Break Even analysis. Methodology: The research method used is an applied method. The research location is the library of Alauddin State Islamic University, Makassar. The research procedure used by the researcher is to compare the results of the Bisection Method, the Regula Falsi Method, and the Secant Method in solving Break-Even Analysis. Main Findings: The results show that the secant method is an efficient method for conducting break-even analysis. This is demonstrated by the error value obtained at the end of the iteration process, which shows the smallest error value. In other experiments, the secant method also showed fewer iterations than other methods. Novelty/Originality of this study: This research can be used as reference material for readers who want to compare the bisection method and the falsi-regularization method. Furthermore, the researchers use the results as a means of evaluating the ability to apply theories in numerical courses.